Dual Role of Autophagy in Regulation of Mesenchymal Stem Cell Senescence - Rastaldo, Raffaella; Vitale, Emanuela; Giachino, Claudia (Frontiers in Cell and Developmental Biology, 2020)
During their development and overall life, mesenchymal stem cells (MSCs) encounter a plethora of internal and external stress signals and therefore, they need to put in action homeostatic changes in order to face these stresses. To this aim, similar to other mammalian cells, MSCs are endowed with two crucial biological responses, autophagy and senescence. Sharing of a number of stimuli like shrinkage of telomeres, oncogenic and oxidative stress, and DNA damage, suggest an intriguingly close relationship between autophagy and senescence. Autophagy is at first reported to suppress MSC senescence by clearing injured cytoplasmic organelles and impaired macromolecules, yet recent investigations also showed that autophagy can promote MSC senescence by inducing the production of senescence-associated secretory proteins (SASP). These apparently contrary contributions of autophagy may mirror an intricate image of autophagic regulation on MSC senescence. We here tackle the pro-senescence and anti-senescence roles of autophagy in MSCs while concentrating on some possible mechanistic explanations of such an intricate liaison. Clarifying the autophagy/senescence relationship in MSCs will help the development of more effective and safer therapeutic strategies.